Analisis Faktor-Faktor yang Memengaruhi Kinerja Ekspor Kopi Indonesia Ke Amerika Serikat - Rastri Paramita (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
This study aims to examine how the influence of the Rupiah exchange rate against the United States Dollar, United States GDP, and Indonesian GDP on the performance of Indonesian coffee exports to the United States in the short and long term. The variable used in this study is the number of Indonesian coffee exports to the United States (XKUSA) (Trademap) as the dependent variable. Meanwhile, the independent variable consists of national income as a proxy for Indonesia's GDP (GDPI) (World Bank) and the United States GDP (GDP USA) (macrotrends) and the exchange rate of the Rupiah against the United States Dollar (NT) (fred.stlouisfed). The data analysis method used is the Error Correction Model (ECM). The results showed that the effect of the exchange rate on the performance of Indonesian coffee exports to the United States showed that the exchange rate variable was not significant in the short or long term. Both Indonesia's GDP and the United States' GDP have no effect on the demand for Indonesian coffee in the short term but have a significant effect in the long term. In the long term, Indonesia's GDP has a negative effect on Indonesian coffee exports to the United States. Meanwhile, the GDP of the United States has a significant positive effect on Indonesia's coffee exports to the United States.